PERLINDUNGAN HUKUM TERHADAP KONSUMEN LIPSTIK YANG TIDAK MEMILIKI LABEL KADALUARSA DI KOTA PEKANBARU - Manurung, Yulika Donna; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Consumer protection at the moment can not be separated from trading activities. In this trading activity, it is expected to create a balance of rights and obligations between business actors and consumers. In Indonesia today consumer protection gets considerable attention because it involves rules for welfare. With the balance between business actors and consumers can create prosperous and prosperous people.The rights and obligations attached to the producer and the consumer are the embodiments of the principle of benefit, the principle of fairness, equilibrium, security, consumer safety, legal certainty, which impacts responsibility to both parties, that a responsibility will not be born if either of the two it does not exist. The right will not be fulfilled if the obligation is not implemented and vice versa, the obligation can not be fulfilled if no rights will be obtained. Pursuant to the translation in the government regulation determines that the guidance of consumer protection is carried out by the Government as an effort to guarantee the rights of consumers and business actors and the implementation of their respective obligations in accordance with the principle of fairness and / or the principle of balance adopted in the Consumer Protection Act.Legal protection against consumer of lipstick cosmetics which has no expired label in Pekanbaru City for correct, clear and honest information about condition and guarantee of goods and / or service in Law Number 8 Year 1999 About Consumer Protection contained in article and Head of Regulation Food and Drug Supervisory Agency of the Republic of Indonesia Number 19 Year 2015 About Technical Requirements Cosmetics, in fact has been clearly regulated related to the obligation of business actors to provide information as complete as possible to avoid the loss on the cosmetics consumer and cosmetics consumers feel safe and comfortable use the product.Supervision of cosmetic circulation has a broad problem, tend to be complex, and is a joint responsibility between government, society as consumers, and business actors. The participation of the community and business actors in the supervision of cosmetic circulation is important and needs to be improved.Keywords: Consumer Protection-Consumer-Cosmetics